2021
DOI: 10.1002/ecs2.3665
|View full text |Cite
|
Sign up to set email alerts
|

Perilous choices: landscapes of fear for adult birds reduces nestling condition across an urban gradient

Abstract: Predator fear effects influence reproductive outcomes in many species. In non-urban systems, passerines often respond to predator cues by reducing parental investment, resulting in smaller and lighter nestlings. Since trophic interactions in urban areas are highly altered, it is unclear how passerines respond to fear effects in human-altered landscapes. Nestlings of passerines in urban areas also tend to be smaller and lighter than their rural counterparts and are often exposed to high densities of potential p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 70 publications
(137 reference statements)
0
5
0
Order By: Relevance
“…Having to actively avoid humans may strongly encourage vigilance behavior in adult birds. This in turn draws investment away from foraging and provisioning chicks and promotes avoidance of areas of the landscape with high predator activity (57)(58)(59). Juncos perceiving less predation risk from humans may be less vigilant toward competitors as well if they shift energetic investment to parental care.…”
Section: Pedestrian Point Countsmentioning
confidence: 99%
See 1 more Smart Citation
“…Having to actively avoid humans may strongly encourage vigilance behavior in adult birds. This in turn draws investment away from foraging and provisioning chicks and promotes avoidance of areas of the landscape with high predator activity (57)(58)(59). Juncos perceiving less predation risk from humans may be less vigilant toward competitors as well if they shift energetic investment to parental care.…”
Section: Pedestrian Point Countsmentioning
confidence: 99%
“…Because vigilance and nest defense behaviors are associated with trade-offs in parental care (58,59), limiting human disturbance of urban bird populations long-term could potentially improve the overall health and survival of chicks. This trade-off was evident in a pandemic lockdown-era study which measured the body condition of nestling urban great tits (Parus major) in urban parks of two cities during the lockdowns: one in which community park attendance increased, and one in which it decreased.…”
Section: Pedestrian Point Countsmentioning
confidence: 99%
“…However, most previous research did not explore avian groups across a wide-range gradient of urbanization, from undisturbed landscapes to highly urbanized ecosystems (Crooks et al 2004;Minor and Urban 2010;Grade et al 2021;Roselli et al 2021). Current studies that did explore avian communities across urban gradients demonstrated that both species richness and total abundance peaked at non-urbanized or moderately urbanized levels (Sanz and Caula 2015;Ciach and Fröhlich 2017;Xu et al 2018).…”
mentioning
confidence: 94%
“…Urban environments often have a higher density of vertebrate predators such as cats and raccoons compared to rural environments (Haskell et al, 2001), although it is not known whether predation rates differ for urban vs non-urban populations of our study species, the dark-eyed junco (Junco hyemalis). Humans, vehicles, anthropogenic noise, and domestic animals may also be interpreted as potential predators (Frid and Dill, 2002;Davies et al, 2017), and perception of predation risk may affect urban animals regardless of predation rates (Beckerman et al, 2007;Grade et al, 2021;Garitano-Zavala et al, 2022). Here we focus on glucocorticoid hormones because they are known to respond to predation risk (Scheuerlein et al, 2001;Hawlena and Schmitz, 2010;Fischer et al, 2014;Jones et al, 2016) and may mediate physiological and life-history responses to risk such as changes in reproductive rate (Clinchy et al, 2011) and changes in population dynamics (Sheriff et al, 2009;Finn et al, 2023).…”
Section: Introductionmentioning
confidence: 99%